Spectatoriale Geschlechterkonstruktionen: Geschlechtsspezifische Wissens- und Welterzeugung in den französisch- und spanischsprachigen Moralischen Wochenschriften des 18. Jahrhunderts - Völkl, Yvonne (2022)
The study sheds light on the development of modern gender discourses and constructions through the literary-journalistic genre of the Spectators. It offers insight into the stereotypical gender discourses of the emerging bourgeois culture in the 18th century as well as into local particularities within the French- and Spanish-speaking context of the time.